Synergistic Microbicidal Effect of AUR and PEITC Against Staphylococcus aureus Skin Infection - Chen, Haoran; Yang, Ning; Yu, Liang; Li, Jiajia; Zhang, Hui; Zheng, Yahong; Xu, Mengran; Liu, Yanyan; Yang, Yi; Li, Jiabin (Frontiers in Cellular and Infection Microbiology, 2022)
Given the increasing prevalence of Staphylococcus aureus antibiotic resistance, there is an urgent need to repurpose approved drugs with known pharmacology and toxicology as an alternative therapeutic strategy. We have reported that the sustained monotherapy of auranofin (AUR) inevitably resulted in reduced susceptibility or even the emergence of resistance to AUR in S. aureus. However, whether drug combination could increase antibacterial activity while preventing AUR resistance is still unknown. Here, we focused on the important role of AUR combined with phenethyl isothiocyanate (PEITC) in skin infection and determined the synergistic antimicrobial effect on S. aureus by using checkerboard assays and time-kill kinetics analysis. This synergistic antimicrobial activity correlated with increased reactive oxygen species (ROS) generation, disruption of bacterial cell structure, and inhibition of biofilm formation. We also showed that AUR synergized with PEITC effectively restored the susceptibility to AUR via regulating thioredoxin reductase (TrxR) and rescued mice from subcutaneous abscesses through eliminating S. aureus pathogens, including methicillin-resistant S. aureus (MRSA). Collectively, our study indicated that the AUR and PEITC combination had a synergistic antimicrobial impact on S. aureus in vitro and in vivo. These results suggest that AUR and PEITC treatment may be a promising option for S. aureus infection.